2018
DOI: 10.3390/coatings8060203
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenesis and Antibacterial Activity of Graphene Oxide and Dexamethasone Coatings on Porous Polyetheretherketone via Polydopamine-Assisted Chemistry

Abstract: Endowing implants with antibacterial ability and osteogenic ability plays important roles in preventing post-operative bacterial contamination and facilitating integration between implants and osseous tissue, consequently reducing implant failure rates. In this study, we develop a facile and versatile strategy with dopamine as an auxiliary for construction of dexamethasone (Dex)/liposome porous coatings. In detail, the surfaces of sulfonated polyetheretherketone (SP) plates are coated with polydopamine firstly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…The drugs include bone morphogenetic protein-2 (BMP-2), alendronate, dexamethasone, etc. All of the drugs showed that GO plays a synergistic role in bone differentiation [ 19 , 20 , 21 ]. In this study, simvastatin (Sim), a new drug candidate in the bone regeneration field, was combined with GO to produce a compound that may be effective for bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The drugs include bone morphogenetic protein-2 (BMP-2), alendronate, dexamethasone, etc. All of the drugs showed that GO plays a synergistic role in bone differentiation [ 19 , 20 , 21 ]. In this study, simvastatin (Sim), a new drug candidate in the bone regeneration field, was combined with GO to produce a compound that may be effective for bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies are summarized and illustrated at Figure 2 and are listed as follows: PEEK sulfonation process, which can be employed either to produce a 3D network on polymer surface [ 39 ], or to embed therapeutic compounds (e.g., lactams [ 45 , 46 ], mouse beta-defensin [ 59 ]). Further surface treatments were also employed after the sulfonation process, such as chlorogenic acid/grafting peptide [ 43 ], graphene oxide coating [ 61 ] and hydrothermal treatment [ 48 ]. Incorporation of therapeutic and/or bioactive agents in the PEEK matrix or on the PEEK surface, such as simvastatin-PLLA [ 39 ]; Ag and Zn ions [ 37 , 39 , 40 , 58 ], dexamethasone plus minocycline-loaded liposomes [ 57 ], bioactive titanium dioxide (TiO 2 ) [ 52 ], 2-methacryloyloxyethyl phosphorylcholine [ 51 ] and titanium plasma [ 56 ].…”
Section: Strategies To Reduce Biofilm Formation In Peek Materials mentioning
confidence: 99%
“…PEEK sulfonation process, which can be employed either to produce a 3D network on polymer surface [ 39 ], or to embed therapeutic compounds (e.g., lactams [ 45 , 46 ], mouse beta-defensin [ 59 ]). Further surface treatments were also employed after the sulfonation process, such as chlorogenic acid/grafting peptide [ 43 ], graphene oxide coating [ 61 ] and hydrothermal treatment [ 48 ].…”
Section: Strategies To Reduce Biofilm Formation In Peek Materials mentioning
confidence: 99%
“…In addition, they also indicate that this antibacterial effect is related to the charge transfer between GO and bacterial cells. 27,28 Therefore, GO has been deeply researched and applied in the fields of biomaterials and biomedicine, such as biosensors, drug delivery, nanoprobes, and tissue engineering scaffold. 29−32 However, to the best of our knowledge, the use of SF and GO composite as surface interfacial layers to modify the Zn sheets is never reported in the literature.…”
Section: Introductionmentioning
confidence: 99%